2000
DOI: 10.1677/joe.0.1660111
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-induced insulin secretion from islets of fasted rats: modulation by alternate fuel and neurohumoral agonists

Abstract: Islets from fed and 24-h-fasted rats were studied immediately after collagenase isolation. (1) After a 24-h fast, the insulin secretory responses to 8 mM glucose measured during perifusion were reduced by more than 90% from islets of fasted donors. (2) Increasing glucose to 11 or 27·5 mM resulted in enhanced insulin secretion from islets of fasted animals. (3) Fasting did not reduce islet insulin content. (4) Responses to 8 or 27·5 mM glucose were not affected if fatty acid-free albumin was used during the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…As it is known, Cch potentiates secretion, increasing the production of IP3 and DAG [35]. Although we have not addressed this issue in this work, we are tempted to speculated that, due to the calorie restriction, it is possible that in the CR rats there is an exacerbation of the cholinergic systems making the islets more sensitive to Ach and consequently to Cch.…”
Section: Discussionmentioning
confidence: 86%
“…As it is known, Cch potentiates secretion, increasing the production of IP3 and DAG [35]. Although we have not addressed this issue in this work, we are tempted to speculated that, due to the calorie restriction, it is possible that in the CR rats there is an exacerbation of the cholinergic systems making the islets more sensitive to Ach and consequently to Cch.…”
Section: Discussionmentioning
confidence: 86%
“…127 Insulin sensitivity worsens in both type II diabetes and in obese subjects during a 60 h fast. 128 Starvation markedly diminished insulin secretion from β cells in rat, 129,130 which is a reversible condition, 131,132 and inhibition of insulin secretion by rapamycin is also a reversible condition.…”
Section: Hunger Diabetesmentioning
confidence: 99%
“…Although the importance of class I PI3Ks in the control of β cell mass and survival is well established, conflicting evidence exists in the literature about their role in insulin secretion. It has been reported that the classical PI3Ks inhibitors wortmannin and LY294002 enhance insulin secretion in rat (5) and mouse islets (6) and pancreatic β cell lines (7) and that wortmannin does not inhibit insulin secretion or synthesis (8). However, knock-out mice for the class I isoform p110γ lack the first phase of insulin secretion (9, 10), and specific blockade of p110γ impairs insulin secretion (11).…”
Section: Introductionmentioning
confidence: 99%